2018
DOI: 10.1186/s12915-018-0483-x
|View full text |Cite
|
Sign up to set email alerts
|

ADMP controls the size of Spemann's organizer through a network of self-regulating expansion-restriction signals

Abstract: BackgroundThe bone morphogenetic protein (BMP) signaling gradient is central for dorsoventral patterning in amphibian embryos. This gradient is established through the interaction of several BMPs and BMP antagonists and modulators, some secreted by Spemann's organizer, a cluster of cells coordinating embryonic development. Anti-dorsalizing morphogenetic protein (ADMP), a BMP-like transforming growth factor beta ligand, negatively affects the formation of the organizer, although it is robustly expressed within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Like Tribolium , Gryllus possesses a homolog of BMP9, a ligand whose function has only been characterised in vertebrates so far. Like Nasonia , Gryllus possesses a homolog of ADMP, a BMP-like ligand that is involved in size regulation during early DV axis formation in vertebrates ( Leibovich et al, 2018 ). Interestingly, unlike any other insect studied so far Gryllus possess a homolog of BMP3, a ligand with inhibitory effects on BMP signalling ( Daluiski et al, 2001 ; Figure 2—figure supplement 1 , Supplementary file 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Like Tribolium , Gryllus possesses a homolog of BMP9, a ligand whose function has only been characterised in vertebrates so far. Like Nasonia , Gryllus possesses a homolog of ADMP, a BMP-like ligand that is involved in size regulation during early DV axis formation in vertebrates ( Leibovich et al, 2018 ). Interestingly, unlike any other insect studied so far Gryllus possess a homolog of BMP3, a ligand with inhibitory effects on BMP signalling ( Daluiski et al, 2001 ; Figure 2—figure supplement 1 , Supplementary file 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The following primers were used for RT-qPCR: chrd.1 F: ACTGCCAGGACTGGATGGT, chrd.1 R: GGCAGGATTTAGAGTTGCTTC ( Leibovich et al, 2018 ); gsc F: TTCACCGATGAACAACTGGA, gsc R: TTCCACTTTTGGGCATTTTC ( Leibovich et al, 2018 ); histone H4 F: GGCAAAGGAGGAAAAGGACTG, histone H4 R: GGTGATGCCCTGGATGTTGT ( Cao et al, 2007 ); mix1 F: CAAAAGCCACCAAGCCCATT, mix1 R: TGCTGAAGGAAACATTGCCC ( Sun et al, 2015 ); sox2 F: GAGGATGGACACTTATGCCCAC, sox2 R: GGACATGCTGTAGGTAGGCGA E.M. (De Robertis ).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent studies have found that the dorsal organizer secretes another BMP protein—Admp—which is inhibited by Chordin. This forms a part of the feedback regulation of the Chordin/BMP system ( Reversade and De Robertis, 2005 ; Leibovich et al, 2018 ). Admp is specifically expressed in the Xenopus organizer, sharing similar sequence and ventral-promoting effects with other ventrally-expressed BMPs like BMP2/4/7 ( Kimelman and Pyati, 2005 ; Reversade and De Robertis, 2005 ; Leibovich et al, 2018 ).…”
Section: Robustness Of Bmp Gradients In DV Pattern Formationmentioning
confidence: 99%
“…This forms a part of the feedback regulation of the Chordin/BMP system ( Reversade and De Robertis, 2005 ; Leibovich et al, 2018 ). Admp is specifically expressed in the Xenopus organizer, sharing similar sequence and ventral-promoting effects with other ventrally-expressed BMPs like BMP2/4/7 ( Kimelman and Pyati, 2005 ; Reversade and De Robertis, 2005 ; Leibovich et al, 2018 ). As a result, only the depletion of all four BMPs results in a complete loss of ventral fate ( Reversade and De Robertis, 2005 ).…”
Section: Robustness Of Bmp Gradients In DV Pattern Formationmentioning
confidence: 99%
See 1 more Smart Citation